1995
DOI: 10.1093/bja/74.4.430
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunoassay for plasma histamine: a study of false positive and false negative values

Abstract: In order to achieve a correct diagnosis of drug anaphylaxis using a radioimmunoassay devoid of interferences, we have studied factors leading to false positive or false negative values of plasma histamine. Different steps in sample collection were studied systematically in 30 normal volunteers. False positive values were found in haemolysed samples, with histamine concentrations being correlated with haemoglobin concentrations, and where plasma was aspirated from the white-cell layer. There was no significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…Previous studies have shown that half-life of plasma histamine and plasma troponin I measures in minutes and days, respectively [47, 48]. Because of troponin long half-life, it is not useful for detection of early reinfarction, which is why the rise of histamine blood concentration may be a parameter for detection of such events.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that half-life of plasma histamine and plasma troponin I measures in minutes and days, respectively [47, 48]. Because of troponin long half-life, it is not useful for detection of early reinfarction, which is why the rise of histamine blood concentration may be a parameter for detection of such events.…”
Section: Discussionmentioning
confidence: 99%
“…LHR test. Blood (1 ml) was collected through the tail vein in eight IRs and six NIRs on D 21 , following immunization in accordance with the literature [20]. Histamine radioimmunologic assay (RIA) was performed using the method of Immunotech (Luminy, France, sensitivity 0.2 nM with a negligible cross-reaction with histamine metabolites and histidine).…”
Section: Methodsmentioning
confidence: 99%
“…Histamine should be assayed within the first hour of a suspected anaphylactic reaction, and in mild cases, only early measurements should be increased [32]. Histamine assay should be avoided during pregnancy (particularly near term) and in patients receiving high doses of heparin, because of a high rate of false negativity.…”
Section: Tryptase and Histaminementioning
confidence: 99%